Percutaneous triamcinolone injection for upper eyelid retraction in thyroid eye disease - Parsons, Shaun R.; Wilson-Pogmore, Ario; Sullivan, Timothy J. (Frontiers in Ophthalmology, 2024)
PurposeTo evaluate percutaneous triamcinolone (TA) injection efficacy in treating upper eyelid retraction (UER) for Australian thyroid eye disease (TED) patients.MethodsWe conducted a retrospective analysis across 8 years and multiple diverse Australian centres identified UER patients who received TA injections. A single operator administered 40mg/1ml TA through upper eyelid skin. Assessments at 4-6 weeks and subsequent eyelid measurements gauged treatment response and complications.Results24 patients and 25 eyelids were included in the study. 91.6% were female, mean age 40.8 ± 10.3 years with mean follow-up of 17.5 months (± 18.5). Pre-treatment MRD1 was 6.2mm ± 1.4, and we observed a mean improvement of 2.2mm from pre-treatment to post-treatment (p<0.001). The mean UER measurement before treatment (defined as MRD1 - 4.0mm) was 3.0mm ± 1.3 (range, 0-6mm). After treatment, the mean UER measurement was -0.1mm. Quality of life (QOL) assessment improved significantly, from pre-treatment score of 4.13 ± 2.4 to post-treatment 8.0 ±1.7 (p<0.001).ConclusionsPercutaneous injection of TA is an effective and safe treatment option for UER in patients with TED. This technique can be performed without upper eyelid eversion, which makes it more tolerable for patients and less complex for the operator compared to the transconjunctival injection approach. Our results show a significant improvement in MRD1 and UER, as well as patient QOL. Moreover, we found a low rate of complications (4.2% induced ptosis) and no cases of raised intraocular pressure. Percutaneous TA injection can greatly reduce the need for eyelid lowering surgery in this patient population.